Pain in an osseous lymphoma. A case presentation. - José Julio Ojeda González; Evangelina Dávila Cabo de Villa; Alexis Guillén Sánchez (Medisur, 2003)
This is a 79 year-old, white, male patient suffering from osseous lymphoma, a less frequent illness, came to the university Hospital Dr. Gustavo Aldereguía Lima¨ in Cienfuegos city, Cuba complaining of intercostal pain in the left hemithorax. This pain was not relieved with the regular medical treatment, that´s why the anesthesia service doctors gave assistance. Costal osteolysis at level D7, D8 and D9 were shown in a thorax X ray. He was treated with analgesic through peridural via such as morphine, local anesthetic. Betametasone was used as anti-inflammatory having positive results. The use of ethylic alcohol as agents contributed to the patient´s improvement and to get back to his normal life.